Difusi Inovasi melalui Model Hybrid Learning dalam pembelajaran Fiqih Di MI Safinatul Huda (SAFINDA) Surabaya - nafisah, zahrotun (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Hybrid Learning learning model is an online-based learning model that utilizes advanced technology and the internet as a learning tool without space and time limits. Hybrid Learning model is one form of diffusion of innovation, where the diffusion of innovation itself is the process of communicating an idea or new idea so that it can be adopted as a whole or limited and accepted by individuals or groups. The Hybrid Learning model was studied at MI Safinatul Huda Surabaya in the subject of Fiqh which was taught by Ustadzah Siti Masruroh. Implementation of the Hybrid Learning Model is carried out at the home of each student with the help of parents. Previously the teacher had given directions and steps to follow the learning Hybrid Learning model at regular meetings between the Parents and the teacher every month. Hybrid Learning model is expected to be able to provide benefits 1) learners get additional learning in addition to school, 2) time to play gadgets at home is reduced by replacing learning while playing, 3) participation of parents' role in children's growth and development in the learning process of Fiqh subjects online .